2015
DOI: 10.1074/jbc.m114.631689
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-associated Domain-containing Ubiquitin Regulatory X (UBX) Protein UBXN1 Is a Negative Regulator of Nuclear Factor κB (NF-κB) Signaling

Abstract: Background:Excessive NF-B hyperactivation should be tightly controlled in cells. Results: UBXN1 inhibits TNF␣-triggered NF-B signaling by sequestering cIAPs from being recruited to TNFR1. Conclusion: UBXN1 is a novel negative regulator of TNF␣-triggered NF-B signaling. Significance: Our study identified a novel ubiquitin-linked protein UBXN1 as a negative regulator of NF-B signaling pathway independent of VCP/p97 and provided important insight into the new regulatory mechanism of the UBX protein family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…The negative regulatory functions of FAF1 and p47 in the NF-κB pathway were previously covered in an earlier part of this review [93,108]. However, the overexpression experiments showed that UBXN1 has the strongest inhibiting ability on TNFα-triggered NF-κB activity in comparison to p47 and FAF1 [123]. Further experiments in cancer as well as immortalized noncancerous cell lines showed that knockdown of UBXN1 potentiates TNFα-triggered NF-κB signaling, suggesting UBXN1 is a physiological suppressor of the NF-κB pathway [123].…”
Section: Ubxn1 An Inhibitor Of Cellular Inhibitors Of Apoptosismentioning
confidence: 94%
See 4 more Smart Citations
“…The negative regulatory functions of FAF1 and p47 in the NF-κB pathway were previously covered in an earlier part of this review [93,108]. However, the overexpression experiments showed that UBXN1 has the strongest inhibiting ability on TNFα-triggered NF-κB activity in comparison to p47 and FAF1 [123]. Further experiments in cancer as well as immortalized noncancerous cell lines showed that knockdown of UBXN1 potentiates TNFα-triggered NF-κB signaling, suggesting UBXN1 is a physiological suppressor of the NF-κB pathway [123].…”
Section: Ubxn1 An Inhibitor Of Cellular Inhibitors Of Apoptosismentioning
confidence: 94%
“…A siRNA screen of UBA domain-containing proteins revealed that silencing three members of the UBXD family, UBXN1, p47, and FAF1, can markedly potentiate TNFα-triggered NF-κB activation [123]. The negative regulatory functions of FAF1 and p47 in the NF-κB pathway were previously covered in an earlier part of this review [93,108].…”
Section: Ubxn1 An Inhibitor Of Cellular Inhibitors Of Apoptosismentioning
confidence: 99%
See 3 more Smart Citations